(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. Sustainable land management has become one of the key topics in environmental change research, particularly in the context of global ecological challenges. Its core lies in ensuring the optimal use of land and the protection of its resource base for future generations. The purpose of the article. The article aims to develop the theoretical and methodological provisions of sustainable land management. Methods. The study employs a range of general and specialized methods, including analysis and synthesis, induction and deduction, comparison, among others. Results. The article, based on a review and synthesis of works by domestic and foreign researchers, further develops the theoretical and methodological foundations of sustainable land management as a key tool for the rational use, protection, and restoration of land resources. This approach ensures the synergy of economic, social, and environmental dimensions. The research methodology is grounded in the integration of general and specific methods aimed at the rational use, conservation, and reproduction of land resources. The object of sustainable land management is the process of land resource utilization within its social, economic, and environmental dimensions. The subject encompasses the complex relationships that arise in the process of land use. The principles of sustainable land management play a crucial role in ensuring the harmonious functioning of the system. The functions of sustainable land management encompass key managerial processes such as planning, organizing, motivating, and controlling, which ensure the effective use, conservation, and restoration of land resources. Based on the studied approaches, the article formulates an original definition of the studied category: sustainable land management is a multifaceted system of land resource management that integrates social, economic, and environmental approaches to ensure balanced use, protection, and restoration of land resources. Its essence lies in achieving a harmonious balance between the needs of modern society and the preservation of natural conditions for future generations through the implementation of innovative technologies, effective management decisions, and responsible land use policies. Conclusions. The article advances the theoretical and methodological provisions of sustainable land management, taking into account modern social, economic, and environmental challenges. The importance of an interdisciplinary approach to ensuring the sustainability of land management is emphasized. The necessity of integrating the principles of rational use, protection, and restoration of land resources is established. Sustainable land management is defined as a multifaceted system that ensures a balance between rational land use, meeting societal needs, and preserving soils for future generations.